(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The development of information and communication technology has significantly transformed patterns of social interaction, particularly through social media and digital platforms. Within this context, the defamation offense regulated under the Electronic Information and Transactions Law (UU ITE) has become a controversial issue, as it is often perceived to potentially suppress freedom of expression. This study aims to analyze the transformation of defamation offenses in the digital era and assess the relevance of UU ITE articles following the second amendment through Law No. 1 of 2024. Using a normative-juridical approach and qualitative analysis of regulations, legal documents, and court decisions, this research finds that the revision of UU ITE has narrowed the scope for multiple interpretations by removing the element of “insult” and clarifying the legal subject. Although normatively improved, the implementation of these provisions in practice still faces challenges, such as inconsistent understanding among law enforcement officers and the lack of digital legal literacy among the public. Therefore, the relevance and effectiveness of these provisions heavily depend on fair law enforcement, public legal education, and the establishment of implementing regulations that uphold human rights protection and freedom of expression in the digital age.